2020
DOI: 10.1542/2019-1895d
|View full text |Cite
|
Sign up to set email alerts
|

The Autism Treatment Network: Bringing Best Practices to All Children With Autism

Abstract: The Autism Treatment Network and Autism Intervention Research Network on Physical Health were established in 2008 with goals of improving understanding of the medical aspects of autism spectrum disorders. Over the past decade, the combined network has conducted .2 dozen clinical studies, established clinical pathways for best practice, developed tool kits for professionals and families to support better care, and disseminated these works through numerous presentations at scientific meetings and publications in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…This study has implications for families of autistic youth with both idiopathic and identified genetic origins. For instance, our findings suggest that sleep onset should be a focus area for generating recommendations and resources for parents of a child with ASD, aligned with current efforts from private foundations and family groups (e.g., Autism Speaks Sleep Toolkit; Coury et al, 2020) and opportunities for clinical intervention . However, there are several critical limitations to consider.…”
Section: Limitationsmentioning
confidence: 72%
“…This study has implications for families of autistic youth with both idiopathic and identified genetic origins. For instance, our findings suggest that sleep onset should be a focus area for generating recommendations and resources for parents of a child with ASD, aligned with current efforts from private foundations and family groups (e.g., Autism Speaks Sleep Toolkit; Coury et al, 2020) and opportunities for clinical intervention . However, there are several critical limitations to consider.…”
Section: Limitationsmentioning
confidence: 72%
“…Additional questionnaires, necessary for addressing key scientific questions, will be added in the near future. These include measures of parental characteristics such as the Parenting Stress Index (Abidin et al 2013) and Beck Depression Inventory (Jackson-Koku 2016), measures of children's ADHD symptoms such as the Conner's rating scale (Keith Conners et al 1998), measures of children's anxiety symptoms such as the SCARED questionnaire (Birmaher et al 1999), and ASD screening measures such as the Social Responsiveness Scale (Constantino 2012), and the Modified Checklist for Autism in Toddlers (Robins et al 2001).…”
Section: Interviews and Questionnairesmentioning
confidence: 99%
“…1 Autism can typically be reliably diagnosed by age 2, but associated developmental delays can appear even earlier. 2 The Autism Speaks Autism Treatment Network (ATN) and Autism Intervention Research Network on Physical Health (AIR-P) have more than a decade of work in the care, treatment, and research of ASDs (see Coury et al 3 in this issue). Families, caregivers, and self-advocates have a strong and equal voice in all aspects of ATN and AIR-P work to ensure that network-related activities and goals are aligned with those in the autism community.…”
Section: The Autism Speaks Autism Treatment Network and Autism Intervention Research Network On Physical Healthmentioning
confidence: 99%